PENGARUH MUTU PELAYANAN RAWAT JALAN TERHADAP PERSEPSI PASIEN/KELUARGA DI RS MISI LEBAK BANTEN - Sarma Eko Natalia Sinaga (Jurnal Kesehatan Manarang, 2017)
Quality of health services for patients is a sense of satisfaction with the health services received. Where the good quality is associated with recovery from illness, improvement of health status, good health service, physical facility, official friendliness, easy procedure and reasonable cost. The purpose of this study illustrates the effect of quality of outpatient services (age, responsiveness, tangibles) on patient and family perception at the RS Lebak Mission. The study design is descriptive with cross-sectional approach, in which a large sample of 110 respondents that are outpatients that have received health services. The independent variables in this study are age, responsiveness, tangibles while the dependent variable is the perception of patient and family. The Data collection is using questioners and the data analysis used univariate analysis and bivariat Chi-Square Test. From the statistical test obtained results that there is a relationship between responsiveness to the quality of outpatient services (P = 0.000). The relationship between tangibles to the quality of outpatient services (P = 0.000). Hospitals should be able to provide physical facilities, the provision of the best care equipment, maintaining the cleanliness and neatness of the room in hospital. In addition, health workers should have the desire to provide the best assistance to patients.